A master builder [videorecording (DVD)] - Shawn, Wallace; Shawn, Wallace; Shawn, Wallace; Quinn, Declan, 1957-; Gregory, André; Hagerty, Julie; Ibsen, Henrik, 1828-1906 (Criterion collection, 2015)
A visionary yet tyrannical middle-aged architect is haunted by figures from his past.